Penggunaan Pembelajaran Model Stad Untuk Meningkatkan Hasil Dan Aktivitas Belajar Siswa Dalam Pemahaman Hak Asasi Manusia Pada Siswa Kelas X IPS 2 Di SMAN 8 Pandeglang - Kustoro Kustoro (Universitas Mathla'ul Anwar Banten, 2020)
This study aims to improve student learning outcomes and activities in the human rights learning process through the STAD learning model. This classroom action research consists of 3 cycles, with 4 stages, namely planning, implementing, observing, and reflecting. The research was conducted on 29 students, class X IPS 2 SMA Negeri 8 Pandeglang in the academic year 2015/2016. The completeness of the learning outcomes of PPKN in the cognitive domain of class X IPSSMA Negeri 8 Pandeglang in the academic year 2015/2016 before the study was 14% and the average learning outcome was 47. After learning by using the STAD (Student Team Achievement Development) Learning Model there was an increase in the completeness of learning outcomes in the cognitive domain of cycles II and III, from 41% to 48% and the average learning outcomes increased from 66 to 75. Student activity increased from cycles I, II and III, namely 14, 22 and 34 from a maximum score of 48 with active percentages of 29%, 46% and 71%. Based on the results of the study, the application of the STAD model of learning can improve PPKN learning outcomes and student activities in the learning process of teaching human rights at SMA Negeri 8 Pandeglang